Identidades Notables

Efectúa aplicando las identidades notables:

- (-2x^3+3x^2)^2
- (-3x^2-4x^4)^2
- (3x+2x^2) \cdot (3x-2x^2)

SOLUCIÓN

- (-2x^3+3x^2)^2
Usaremos la fórmula:
(a+b)^2 = a^2 + b^2 + 2ab

(\underbrace{-2x^3}_{a}+\underbrace{3x^2}_{b})^2 =

\left( -2x^3 \right)^2 + \left( 3x^2 \right)^2 + 2 \cdot (-2x^3) \cdot (3x^2) =


(-2)^2 \cdot \left(x^3 \right)^2 + 3^2 \cdot \left( x^2 \right)^2 + 2 \cdot (-2x^3) \cdot (3x^2) =


4 \cdot x^6 + 9 \cdot x^4  -12 x^5 =


4x^6 -12 x^5 + 9 x^4

- (-3x^2-4x^4)^2
Usaremos la fórmula:
(a-b)^2 = a^2 + b^2 - 2ab

(\underbrace{-3x^2}_{a}-\underbrace{4x^4}_{b})^2 =


\left( -3x^2 \right)^2 +   \left( 4x^4 \right)^2   - 2 (-3x^2)(4x^4) =


9x^4 + 16x^8 + 24x^6=


 16x^8 + 24x^6 + 9x^4

- (3x+2x^2) \cdot (3x-2x^2)
La fórmula a usar es:
(a+b) \cdot (a-b) = a^2 - b^2

(\underbrace{3x}_{a}+\underbrace{2x^2}_{b}) \cdot = (\underbrace{3x}_{a}-\underbrace{2x^2}_{b})=


(3x)^2 - \left(2x^2 \right)^2=


9x^2 - 4x^4=


- 4x^4 + 9x^2